IT-Based Training of Trainer (TOT) Zakat and Wakf Management Training/ Application for Zakat Collection Units (UPZ) City of Palangka Raya - Hasan, Ahmadi; Kurniawan, Rahmad; Dakhoir, Ahmad; Sadikin Abdul Azis Mandala Putra, Jay; Adi Astiti, Ni Nyoman (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2022)
The main purpose of Community Service (PKM) is to bring educational institutions closer to the community, so that universities can help the community in the fields of education, counseling, developing human resources and community knowledge and prospering the economy. The targets of this Community Service (PKM) activity are zakat managers or zakat collectors in Palangka Raya City as well as the local community. So we need programs / activities related to zakat amil who carry out zakat management manually. So that this activity is carried out to develop the resources and knowledge of zakat amil in managing zakat more professionally and using technology. The implementation of community service activities at the Faculty of Economics and Islamic Business IAIN Palangka Raya has been going well and smoothly, the zakat collectors in the Menteng sub-district, Palangka Rata city are very enthusiastic about participating in the activities held.